Memory-Based Quantity Discrimination in Coyotes ( Canis latrans ) - Mahamane, Salif; Grunig, Kevin L.; Baker, Joseph; Young, Julie K.; Jordan, Kerry E. (DigitalCommons@University of Nebraska - Lincoln, 2014)
Previous research has shown that the ratio between competing quantities of food significantly mediates coyotes‘ (Canis latrans) ability to choose the larger of two food options. These previous findings are consistent with predictions made by Weber‘s Law and indicate that coyotes possess quantity discrimination abilities that are similar to other species. Importantly, coyotes‘ discrimination abilities are similar to domestic dogs (Canis lupus familiaris), indicating that quantitative discrimination may remain stable throughout certain species‘ evolution. However, while previously shown in two domestic dogs, it is unknown whether coyotes possess the ability to discriminate visual quantities from memory. Here, we address this question by displaying different ratios of food quantities to 14 coyotes before placing the choices out of sight. The coyotes were then allowed to select one of either non-visible food quantities. Coyotes‘ discrimination of quantity from memory does not follow Weber‘s Law in this particular task. These results suggest that working memory in coyotes may not be adapted to maintain information regarding quantity as well as in domestic dogs. The likelihood of a coyote‘s choosing the large option increased when it was presented with difficult ratios of food options first, before it was later presented with trials using more easily discriminable ratios, and when the large option was placed on one particular side. This suggests that learning or motivation increased across trials when coyotes experienced difficult ratios first, and that location of food may have been more salient in working memory than quantity of food.